2001
DOI: 10.1046/j.0266-4909.2001.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of a virtual field trip to replace a real field trip

Abstract: This study examines student perceptions on the use of virtual field trips (VFT) as part of their university experience and in particular the extent to which they could replace real field trips. While students were extremely positive about the potential of VFT to provide valuable learning experiences (and in particular a VFT constructed by the authors of this paper) nearly all of the students were insistent that it could not, and should not, replace real field trips. Furthermore when the same students were re‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 11 publications
11
87
0
3
Order By: Relevance
“…The combination of tour followed by search activity mitigates the problem of students getting lost in virtual environments (discussed by Spicer & Stratford, 2001;Treves & Bailey, 2012) whilst still engaging them in investigative problem solving. It is also suspected that it encourages them to use zoom controls more than they would although there was no control for this in our experiment, so we did not test this conjecture.…”
Section: ] Students Exploring Paleo-landscapesmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of tour followed by search activity mitigates the problem of students getting lost in virtual environments (discussed by Spicer & Stratford, 2001;Treves & Bailey, 2012) whilst still engaging them in investigative problem solving. It is also suspected that it encourages them to use zoom controls more than they would although there was no control for this in our experiment, so we did not test this conjecture.…”
Section: ] Students Exploring Paleo-landscapesmentioning
confidence: 99%
“…A more sophisticated tracking system would gather data on multiple interactions during a search or activity. This would open up the possibilities of introducing online field notebooks and cross-referencing students' note taking with their explorations around a VFT (Spicer & Stratford, 2001) but, as has been noted, this may impact the ability to easily visualise the data.…”
Section: ] Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although on one hand, mobile AR technologies can represent a communication gap between incoming freshmen and educators (National Higher Education ICT Initiative, 2007;Perlmutter, 2011;Dahlstrom and Bichsel, 2014), studies have shown that simulations, games, and virtual field trips (VFTs) actually increase students' motivation (McGreen and Sánchez, 2005;Bell et al, 2009;Honey and Hilton, 2011;Johnson and Johnston, 2013;Bursztyn et al, 2017). There have been increasing reports of VFTs being used in a variety of college courses, including biology, medicine, engineering, geography, and geology (e.g., Spicer and Stratford, 2001;Liarokapis et al, 2004;Stumpf et al, 2008;Jacobson et al, 2009;Yuen et al, 2011;Lee, 2012;Pringle, 2013;Friess et al, 2016). Results from those studies indicate that Bursztyn et al | Assessment of student learning using augmented reality field trips for mobile smart devices GEOSPHERE | Volume 13 | Number 2 students enjoy using the VFTs, and researchers see gains in interest in the material through the interactivity and immersive experience as compared to traditional learning (Spicer and Stratford, 2001;Stumpf et al, 2008;Jacobson et al, 2009;Pringle, 2013;Friess et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been increasing reports of VFTs being used in a variety of college courses, including biology, medicine, engineering, geography, and geology (e.g., Spicer and Stratford, 2001;Liarokapis et al, 2004;Stumpf et al, 2008;Jacobson et al, 2009;Yuen et al, 2011;Lee, 2012;Pringle, 2013;Friess et al, 2016). Results from those studies indicate that Bursztyn et al | Assessment of student learning using augmented reality field trips for mobile smart devices GEOSPHERE | Volume 13 | Number 2 students enjoy using the VFTs, and researchers see gains in interest in the material through the interactivity and immersive experience as compared to traditional learning (Spicer and Stratford, 2001;Stumpf et al, 2008;Jacobson et al, 2009;Pringle, 2013;Friess et al, 2016). AR usage in medical, engineering, and mathematics education has resulted in similar findings (e.g., Liarokapis et al, 2004;Yuen et al, 2011;Lee, 2012).…”
Section: Introductionmentioning
confidence: 99%